2021
DOI: 10.3390/ijerph18020443
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Parental Impact on Problematic Smartphone Use among Korean Adolescents

Abstract: This study aimed to examine the effective parental impact in preventing problematic smartphone use in adolescents by identifying the parent-related factors. A secondary analysis of cross-sectional data from a Korean national survey was conducted. Data from 2758 male and 2419 female adolescents, aged 10 to 19 years, were analyzed; the respondents were divided into normal and risk groups based on their standardized smartphone addiction diagnostic scale scores. Parent-related factors of smartphone addiction were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…Boys were more likely to be problematic users with a factor of −0.755. This finding is consistent with other studies [ 44 , 46 , 60 , 96 , 97 ] that reported boys were more prone to excessive mobile device use, while several studies reported the opposite [ 45 , 74 ]. However, the majority of these studies were conducted on adolescent and adult populations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Boys were more likely to be problematic users with a factor of −0.755. This finding is consistent with other studies [ 44 , 46 , 60 , 96 , 97 ] that reported boys were more prone to excessive mobile device use, while several studies reported the opposite [ 45 , 74 ]. However, the majority of these studies were conducted on adolescent and adult populations.…”
Section: Discussionsupporting
confidence: 92%
“…Sociodemographic variables, including the child’s gender, the child’s age when starting to use a mobile device, the parent’s educational level, household income, type of applications used, and the purpose of giving a mobile device to the child, were selected as predictive factors. These variables were selected based on previous studies [ 3 , 21 , 32 , 44 , 45 , 46 , 47 ].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Entertainment apps (YouTube, TikTok, Instagram, Pinterest) occupy an important place in teenage girls' online lives. This is consistent with data from other studies, which indicate that girls are more likely to use smartphones for communication, watching videos and listening to music [13,54], for interpersonal communication [13,53,55] and are more active social media users [13,53,56,58].…”
Section: ■ Discussionsupporting
confidence: 91%
“…Most studies show that males are more likely than females to use entertainment software like games, movies or music [53,54]. These gender differences can be tracked from early school age through adolescence into adulthood [55][56][57].…”
Section: ■ Discussionmentioning
confidence: 99%
“…i) The risk factors for smartphone addiction included frequent use of smartphone/tablet SNSs [24], [25]; ii) SNS and social media use predicted problematic smartphone use [26]- [30]; iii) SNS was positively related to symptoms of smartphone addiction/nomophobic behavior [31]- [36]; iv) SNS application usage is more prominent in the addicted group [37]; v) Users who access the Internet for SNSs were linked to a higher smartphone addiction tendency [38]- [46]; vi) SNS use was not related to smartphone dependence [47]; vii) Social network usage purposes were negatively correlated with nomophobic behavior [48]. Chatting (WhatsApp, Facebook Messenger) and Texting/Instant messaging i) The risk factors for smartphone addiction included frequent use of smartphone/tablet instant messaging [24], [25]; ii) Social-recreational onliners (frequently involved in social media activities and instant messaging) showed significantly higher levels of PSU over time [49]; iii) Mobile messenger use predicted problematic smartphone use [50] iv) Smartphone use for texting was significantly associated with higher smartphone addiction behaviors [25], [45]; v) Addiction groups show significantly higher scores on "online chat" [51]; vi) The use of instant messenger was unrelated to smartphone dependence [47], [52].…”
Section: Sample Of Included Studiesmentioning
confidence: 99%